Foreign direct investment and the domestic capital stock - Desai, Mihir A. 1968-; Foley, C. Fritz; Hines, James R. 1958- (National Bureau of Economic Research, 2005)
"This paper evaluates evidence of the impact of outbound foreign direct investment (FDI) on domestic investment rates. OECD countries with high rates of outbound FDI in the 1980s and 1990s exhibited lower domestic investment than other countries, which suggests that FDI and domestic investment are substitutes. U.S. time series data tell a very different story, however: years in which American multinational firms have greater foreign capital expenditures coincide with greater domestic capital spending by the same firms. One dollar of additional foreign capital spending is associated with 3.5 dollars of additional domestic capital spending in the time series, implying that foreign and domestic capital are complements in production by multinational firms. This effect is consistent with cross sectional evidence that firms whose foreign operations expand simultaneously expand their domestic operations, and suggests that interpretation of the OECD cross sectional evidence may be confounded by omitted variables"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Investments -- Econometric models; Investments, Foreign